Exploring the Language Teaching Self-Efficacy Levels of English Language and Literature Department Students: The Impact of Demographic Variables - Akyıldız, Seçil Tümen (My University, 2025)
This study explores the self-efficacy levels of students in the Department of English Language and Literature at Fırat University regarding their ability to teach English. It examines how self-efficacy varies according to gender, academic year, and teaching experience. Using a causal-comparative research design, data were collected from 275 participants through the Language Teaching Self-Efficacy Scale (Deregözü & Gündoğar, 2020). Findings reveal that students demonstrate moderate self-efficacy in planning, performing, and evaluating language teaching. While gender did not significantly impact self-efficacy, academic year played a role—fourth-year students reported the highest levels. No significant differences were found based on teaching experience. The study highlights the need for integrating targeted pedagogical training into the curriculum to strengthen self-efficacy. It also calls for further longitudinal and comparative research to track the development of teaching self-efficacy over time. Due to the scarcity of related studies within English Language and Literature programs, this research contributes a unique perspective. It offers valuable insights into teacher preparation in non-education departments and emphasizes the importance of practice-oriented curricular enhancements to better equip students for future teaching roles.
Keywords: Language teaching; self-efficacay; teaching self-efficacy; English language and literature